Combination of Endobronchial Ultrasound and Modern Cytological Diagnosis in Patients With Intrathoracic Lesions - K. S. Pavlyuk; E. N. Slavnova; M. G. Leonov; E. A. Terman; T. V. Sainoga; T. V. Sinitskaya; O. V. Gospirovich; E. A. Artemova; Zh. B. Yeleubayeva; I. N. Muntyan (Инновационная медицина Кубани)
Objective: To evaluate the effectiveness of endobronchial (EBUS) and endoscopic ultrasound (EUS) in cytomorphological verification of a malignant process using the transbronchial needle aspiration (TBNA) of the lymph nodes and mediastinal organs.Materials and methods: In 2017–2019 we analyzed the cytological samples (standard and cell block) of 172 patients (115 males and 57 females) with an average age of 61 years (25–82 years) in the clinical diagnostic laboratory of Scientific Research Institute – Ochapovsky Regional Clinical Hospital No. 1 (Krasnodar, Russian Federation). Of them 111 were used for immunocytochemical analysis. The majority of the studies (77) were performed in patients with lung cancer in order to identify the stage of the disease. We used combined bronchoscopy under general anesthesia in the operating room with high-frequency ventilation and a rapid on-site evaluation (ROSE).Results: We found the lymph node and mediastinal invasion in 140 (81%) patients who underwent EBUS-EUS TBNA. The non-diagnostic results were obtained in 32 (19%) patients. The combination of EUS and EBUS with TBNA showed the highest effectiveness in the mentioned clinical cases. The sensitivity, specificity, and accuracy of the cytologic analysis during EBUS and EUS with TBNA and no ROSE were 89%, 100%, and 90%, respectively. ROSE reduced the rate of non-diagnostic results and increased the sensitivity (96%), specificity (100%), and accuracy (97%) of the cytologic evaluation.Conclusions: According to the obtained results, we recommend using EBUS-EUS TBNA modalities for morphological verification of the mediastinal lymph nodes as a routine invasive diagnosis component of the preoperative evaluation in patients with lung cancer.